P03 Early experience of a novel intrasaccular flow disrupter for the treatment of intracranial aneurysms – the Contour device. (29th August 2022) - Chung, R-E; Jadun, CK; Nayak, S; Hashim, Z
Abstract : Introduction: The treatment of wide neck bifurcation aneurysm has always been challenging and devices like the Woven EndoBridge (WEB) have been used over the years to address this issue. 1 The Contour is a new device designed to act as a flow diverter at the aneurysm neck. 2 Aim of study: We report out centre's early experience in using this device. Methods: Retrospective data analysis performed to identify all patients treated with Contour device at our centre. Total of 7 patients were initially identified with all cases being elective. Two patients were excluded as there were difficulties in deploying the device successfully due to unfavourable anatomy hence device not deployed. Results: 5 patients were treated successfully (4 Trans-radial access, 1 Trans-femoral access) with the Contour device with no procedure related complication (4 female and 1 male). Mean age of 60 years (range 44–71). 3 aneurysms were in the posterior circulation and the other two located within the anterior circulation. Mean average neck width 4.22mm (range 3.3–5mm). Follow up of 3/5 patients at 6 months showed complete aneurysm occlusion and unchanged modified Rankin score of 0. Two patients are pending imaging follow up. Conclusion: Our early experience supports the use of Contour device in treating these difficult to treat aneurysms with initial good occlusion rates and no significant complications. However, device deployment in difficult anatomy can be challenging. Further studies are needed with larger patient numbers and longer term follow up to ensure its long-term efficiency and safety. References: Arthur AS, Molyneux A, Coon AL for the Web-It Study Investigators, et al . The Safety and Effectiveness of the Woven Endobridge (Web) System for the Treatment of Wide-necked Bifurcation Aneurysms: Final 12-month Results of the Pivotal Web Intrasaccular Therapy (Web-It) Study. Journal of Neurointerventional Surgery 2019;11:924–930. Liebig T, Killer-Oberpfalzer M, Gal G, Schramm P, Berlis A, Dorn F, Jansen O, Fiehler J, Wodarg F. The Safety and Effectiveness of the Contour Neurovascular System (Contour) for the Treatment of Bifurcation Aneurysms: The Cerus Study. Neurosurgery . 2021 Dec 29. Doi: 10.1227/Neu.0000000000001783. Epub Ahead of Print. PMID: 35113830. Do you have any conflict of interest to declare? : No